Surface modification of wire-EDMed Ti6Al4V alloy by ultrasonic assisted magnetic abrasive finishing technique - Celik, Mahmut; Gurun, Hakan; Caydas, Ulas (Iop Publishing Ltd, 2022)
In this study, it is aimed to remove the white layer formed on the surface of Ti6Al4V alloy as a result of Wire-Electro Discharge Machining by Magnetic Abrasive Finishing method. In the study, specimens were machined with W-EDM method under constant conditions and were machined at different levels of machining time, abrasive size, the number of revolutions and magnetic field parameters in UAMAF and MAF method. In the study in which Taguchi L18 experimental design was used, a total of 36 experiments were performed for MAF and UAMAF methods. The machined samples were examined by SEM and changes in white layer thickness were recorded. Statistical effects of processing parameters on white layer thickness were determined by the ANOVA method. As a result of the study, it was determined that the white layer thickness could decrease by 84% and 89% for the MAF and UAMAF methods, respectively. It has been also determined that ultrasonic support has a positive effect of 13.45% on average.
Keywords: ultrasonic assisted magnetic abrasive finishing; wire-electrical discharge machining; white layer; Ti6Al4V